2021
DOI: 10.33158/asb.r133.v7.2021
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative and productive performance of two soybean cultivars at different plant densities

Abstract: The spatial arrangement and plant population have been highlighted as fundamental tools for increasing productivity. The objective was to evaluate the vegetative and productive performance of two soybean cultivars at different plant densities. Seeds of soybean cultivars (TMG 7063 IPRO and BS 2606 IPRO), recommended for the Alto Paranaíba region in the state Minas Gerais, were used and sown at seven different densities (8, 10, 12, 14, 16, 18 and 20 plants meter-1, equivalent to 160, 200, 240, 280, 280, 320, 360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…The results of this research showed a significant positive moderate correlation between plant height and height of insertion of the 1 st pod (r = 0.51). This result agrees with some studies, where the authors reported that the increase in the population density of plants per hectare had an influence by providing an increase in soybean height for light interception (Bomtempo et al, 2021). However, there was a strong positive correlation between pod and branches per plant (r = 0.68), as well as, grains per plant with branches and pod per plant (r = 0.69; r = 0.95 respectively), result also evidenced by Mahbub et al (2015), whose pod per plant was the component that most contributed to productivity.…”
Section: Resultssupporting
confidence: 93%
“…The results of this research showed a significant positive moderate correlation between plant height and height of insertion of the 1 st pod (r = 0.51). This result agrees with some studies, where the authors reported that the increase in the population density of plants per hectare had an influence by providing an increase in soybean height for light interception (Bomtempo et al, 2021). However, there was a strong positive correlation between pod and branches per plant (r = 0.68), as well as, grains per plant with branches and pod per plant (r = 0.69; r = 0.95 respectively), result also evidenced by Mahbub et al (2015), whose pod per plant was the component that most contributed to productivity.…”
Section: Resultssupporting
confidence: 93%
“…A transgeneridade é uma experiência identitária (Bomtempo & Mendes, 2020), geralmente marcada por sofrimento e lutas internas. Essa contradição entre o corpo físico e o gênero com o qual o indivíduo se identifica costuma gerar um quadro de desconforto, impulsionando o indivíduo, muitas vezes, a buscar um processo de transição física e social (Sá, 2017).…”
Section: Introductionunclassified
“…The increase in national production has occurred due to improvements in management techniques and genetic improvement programs (Oda et al, 2015). Associated with productivity (the main characteristic of a cultivar) one can consider precocity, resistance/tolerance to biotic and abiotic characteristics to which the plant may be subjected and the introgression of genes of interest in the genotype to be released as a cultivar (Bomtempo, Matsuo, & Oda, 2021;Matsuo, Borém, & Sediyama, 2021).…”
Section: Introductionmentioning
confidence: 99%